Penerapan Model Picture and Picture Berbantuan Media Puzzle Meningkatkan Tanggung Jawab dan Hasil Belajar Siswa - Rahayu Pratiwi; Dwi Anggraini (UNIB Press, 2023)
The research aims to improve the attitude of responsibility and learning outcomes of fourth grade students at SDN 097 North Bengkulu by applying the picture and picture type cooperative model assisted by puzzle media. This research is Classroom Action Research with research subjects totaling 18 students. The instruments used were observation sheets and tests and used the formula for the average score, the highest score, the lowest score, the difference between the scores and the range of values for each data criterion. Test data was analyzed using the formula for average value and percentage of classical learning. The average result of the application of the cooperative model type picture and picture assisted by the first cycle puzzle media was 43.75 in the sufficient category and increased to 69.5 in the very good category. The average result of the attitude of responsibility in the first cycle was 8.5 in the sufficient category and increased to 14.09 in the very good category. The learning outcomes for PPKn subjects on average in cycle I was 69.72 classical completeness 55.55% and increased to 74.67 classical completeness 88.89% in cycle II. The learning outcomes for Indonesian subjects in cycle I averaged 69.36 classical completeness 61.11% and increased to 76.67 classical completeness 88.89% in cycle II. The learning outcomes of IPS subjects in cycle I averaged 70.61 classical completeness 55.55% and increased to 76.25 classical completeness 94.44% in cycle II. The conclusion of the application of the cooperative model type picture and picture assisted by media puzzles can increase the attitude of responsibility and student learning outcomes in thematic learning in class IV SDN 097 North Bengkulu.